ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH DAERAH DAERAH ISTIMEWA YOGYAKARTA - Yulia Rosiandani; Priyastiwi (Universitas Sarjanawiyata Tamansiswa, 2025)
Measuring regional financial performance is important because it is one indicator to determine the success of a region in implementing regional autonomy. This study aims to determine the financial performance of the Regional Government of the Special Region of Yogyakarta in 2019-2024 by using measurement of five financial ratios. This study was conducted at Badan Pengelola Keuangan dan Aset DIY. This study used a quantitative descriptive approach by collecting secondary data contained in the Financial Report 2019-2024. The results of the study indicate that based on the PAD effectiveness ratio, the financial performance of the DIY Regional Government in 2019-2024 can be said to be very effective. The results of the calculation of the regional financial efficiency ratio indicate that financial performance can be said to be efficient. The results of the calculation of the harmony ratio indicate that the financial performance of the DIY Regional Government in 2019-2024 is included in the poor category because the amount of operating expenditures> capital expenditures. The calculation of the regional original revenue growth ratio shows that financial performance in 2019, 2021, 2023, and 2024 was in the very low category. Meanwhile, in 2022, the growth was in the low category. The calculation of the regional financial independence ratio indicates that the financial capacity of the Yogyakarta Regional Government from 2019 to 2024 is moderate and has a participatory relationship pattern.